2015
DOI: 10.1002/cne.23868
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of the neuroligins and neurexins in fragile X mice

Abstract: Neuroligins and neurexins are transsynaptic proteins involved in the maturation of glutamatergic and GABAergic synapses. Research has identified synaptic proteins and function as primary contributors to the development of fragile X syndrome. Fragile X mental retardation protein (FMRP), the protein that is lacking in fragile X syndrome, binds neuroligin-1 and -3 mRNA. Using in situ hybridization, we examined temporal and spatial expression patterns of neuroligin (NLGN) and neurexin (NRXN) mRNAs in the somatosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 117 publications
1
6
0
Order By: Relevance
“…While there was a transient early increase in females, LPS‐treated males demonstrated a long‐term decrease in expression of all three genes. These findings agree with previous studies that found decreased expression of NRXN3 mRNA in male fragile X knockout (FMR1‐KO) mice while expression was increased in females (Lai et al, 2016). NLGNs have a critical role in the balance of inhibitory and excitatory transmission, and mice with NLGN1 deletion exhibited repetitive stereotyped grooming behaviours (Blundell et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…While there was a transient early increase in females, LPS‐treated males demonstrated a long‐term decrease in expression of all three genes. These findings agree with previous studies that found decreased expression of NRXN3 mRNA in male fragile X knockout (FMR1‐KO) mice while expression was increased in females (Lai et al, 2016). NLGNs have a critical role in the balance of inhibitory and excitatory transmission, and mice with NLGN1 deletion exhibited repetitive stereotyped grooming behaviours (Blundell et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…One intriguing possibility is that altered NLGN2 function may result in a sex‐specific phenotype. Sex differences in hippocampal NLGN2 expression have been observed in mice [Lai et al, ] and NLGN2 expression is regulated by 17‐beta‐estradiol and progesterone in rat uterine tissue [Kang et al, ]. Thus, altered NLGN2 function may affect males and females differently.…”
Section: Discussionmentioning
confidence: 99%
“…The dentate gyrus (DG) is a hippocampal subregion that plays a critical role in information processing including spatial memory ( Jonas and Lisman, 2014 ; Bott et al, 2016 ) and the aging-related functional alterations in this region were previously described for rats, mice, and other mammalian models ( Lister and Barnes, 2009 ). The results obtained from FMR1 KO mouse models indicate an important function of FMRP in physiology, structure and connectivity of DG, and the related behavior ( Bostrom et al, 2016 ; Lai et al, 2016 ; Scharkowski et al, 2017 ). Previous studies on rats showed deficits in hippocampal-dependent memory in a FMR1 KO model ( Till et al, 2015 ) and behavior-induced changes of FMRP level in DG ( Irwin et al, 2005 ).…”
Section: Introductionmentioning
confidence: 91%